ANALISIS KOORDINASI PENYUSUNAN RENCANA KERJA PEMERINTAH DAERAH 2022-2023 UNTUK MENINGKATKAN INFRASTRUKTUR DASAR (AIR BERSIH DAN SANITASI LAYAK) DI KABAPUTEN SUMEDANG - Suryana, Dadang; Akadun; Windiasri, Nur Anisa; Cahyani, Nindia Putri; Priyanti, Dewi; Sulistio, Roy Amala (LPPM UNSAP & FISIP UNSAP, 2024)
This research aims to find out the Coordination of Preparing the 2022-2023 Regional Government Work Plan to Improve Basic Infrastructure (Clean Water and Adequate Sanitation) in Sumedang Regency. What factors are the obstacles and how to overcome the obstacles. The research method used in the research is qualitative methodology The research informants were four informants. The data collection techniques used were literature study and field study consisting of observation, interviews and documentation. Meanwhile the processing procedures in this research were data reduction, data presentation, data verification and triangulation. Based on the research results, it was concluded that coordination in preparing regional government work plans to improve basic infrastructure (clean water and adequate sanitation) was considered effective, but target achievement was still below expectations. It is necessary to increase efforts to find solutions to achieve the expected targets in the context of basic infrastructure development in the future. Including inadequate prioritization of basic infrastructure services and lack of coordination in planning. Development planning, especially through the RPJMD, is an important focus for formulating more effective policies in BAPPPPEDA Sumedang district. At the end of writing this research, the researcher provides suggestions, namely that strong collaboration between sectors and government levels, a holistic approach and regular coordination meetings are needed to realize sustainable and comprehensive development goals